Towards a More Efficient Design of High Temperature Concentrating Solar Power Plant With Cascaded Thermal Energy Storage - Brenda Hernandez Corona; Thomas Fasquelle; Muhammad Abdullah; Nicolas Lopez Ferber; Jean-Francois Hoffmann; Mathieu Martins; Ahmad Mayyas; Nicolas Calvet (SolarPACES Conference Proceedings)
This work proposes a novel concentrating solar power (CSP) plant configuration aiming at a high operation temperature of 1000°C. The thermal energy storage system (TES) would be the focus of this research by modifying it and proposing four configurations to enhance the overall efficiency of high-temperature solar power towers. The objective is to identify the most thermodynamically efficient designs by analyzing the literature on the different components and comparing them to a reference base case of a conventional 100 MWe solar power tower plant (2-tank molten salt TES) operating at 565°C. The proposition consists of a Brayton/Rankine combined cycle with a double cascade TES. In the proposed cascade TES, the primary unit consists of a high-temperature air/ceramic packed-bed thermocline operating at 1000°C, while the secondary unit is a single molten salt tank used as sensible heat. The secondary TES is used as a heat sink during charge, improving efficiency and reducing the size of the air/ceramic-packed bed by extracting the thermocline out of the tank. Excess energy stored in the secondary TES is utilized for preheating during discharge. The methodology incorporates evaluating various combinations of solar block, TES, and power block integration. Combinations are selected from a comprehensive literature review. The study focuses on night-time operations. Further analysis of the cost-benefit of the designs would be required to compare the overall energy production and furthermore the LCOE.